Application of Article 3 of the Journalistic Code of Ethics in the News Case "The Child of a Tax Officer Becomes the Perpetrator" on the Online Media Platform Jawapos.Com 24 February 2023 Edition March 05, 2023 - Ega Oktasya Putri Frianda; Dwi Prasetyo (Jurnal Spektrum Komunikasi, 2023)
This research is based on observations of several news articles. In order to find out more about the application of the journalistic code of ethics in the news, especially in article 3, the author wrote in a news story "Children of Tax Officials Become Perpetrators of Persecution" on the online media platform JawaPos.com edition 24 February 2023- 05 March 2023. Descriptive qualitative methods will be used in this research. The author will make observations and analysis on the news "Tax Official's Children Become Perpetrators of Persecution" on the online media platform JawaPos.com. This research analyzes the application of article 3 of the journalistic code of ethics which is divided into four interpretations. The results of this research show that there is application of article 3 of the journalistic code of ethics in every news published in accordance with the edition of 24 February 2023- 05 March 2023.